Dark Costs, Missing Data: Shedding Some Light on Services Trade - James E. Anderson; Ingo Borchert; Aaditya Mattoo; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2015)
A structural gravity model is used to estimate barriers to services trade across many sectors, countries and time. Since the disaggregated output data needed to flexibly infer border barriers are often missing for services, we derive a novel methodology for projecting output data. The empirical implementation sheds light on the role of institutions, geography, size and digital infrastructure as determinants of border barriers. We find that border barriers have generally fallen over time but there are differences across sectors and countries. Notably, border effects for the smallest economies have remained stable, giving rise to a divergent pattern across countries.
Keywords: F13; F14; F16; 330; gravity; services trade; trade costs in services; home bias; border effects